Diksyunaryo Filipino Filipino 2000. (Sangay ng mga Paaralang Lungsod, 2000)
A monolingual, prescriptive dictionary that aims to promote the usage of the Filipino language. Aside from the definitions, words are used in sentences to show their proper usage.